2023
DOI: 10.1038/s41598-023-45302-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of resting-state functional connectivity in the lumbar spinal cord with 3T MRI

Anna Combes,
Lipika Narisetti,
Anirban Sengupta
et al.

Abstract: Functional MRI (fMRI) of the spinal cord is an expanding area of research with potential to investigate neuronal activity in the central nervous system. We aimed to characterize the functional connectivity features of the human lumbar spinal cord using resting-state fMRI (rs-fMRI) at 3T, using region-based and data-driven analysis approaches. A 3D multi-shot gradient echo resting-state blood oxygenation level dependent-sensitive rs-fMRI protocol was implemented in 26 healthy participants. Average temporal sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(78 reference statements)
1
5
1
Order By: Relevance
“…A subsequent slice-wise seed-to-voxels analysis, similar to the approach employed by (Barry et al, 2016), further underscored the presence of these bilateral motor networks. This corroborates the findings of Combes and colleagues (Combes et al, 2023), who similarly emphasized substantial connectivity between the ventral horns. However, it is noteworthy that the ventral connectivity reported in their study demonstrated an amplitude more than fourfold stronger than our observations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A subsequent slice-wise seed-to-voxels analysis, similar to the approach employed by (Barry et al, 2016), further underscored the presence of these bilateral motor networks. This corroborates the findings of Combes and colleagues (Combes et al, 2023), who similarly emphasized substantial connectivity between the ventral horns. However, it is noteworthy that the ventral connectivity reported in their study demonstrated an amplitude more than fourfold stronger than our observations.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we did not observe significant connectivity either within (i.e., dorso-ventral) or between (i.e., left dorsal -right ventral and right dorsal -left ventral) hemicords. Such patterns have been observed in the lumbosacral (Combes et al, 2023) and cervical spinal cord (Eippert et al, 2017b;Kaptan et al, 2023;Weber et al, 2018). While these dorso-ventral connections may potentially support polysynaptic spinal reflexes (Sandrini et al, 2005), it is important to emphasize that they seem to be strongly influenced by the specific processing approach (Eippert et al, 2017a;Kaptan et al, 2023) and have exhibited poor reliability (Kaptan et al, 2023).…”
Section: Extension Of Static Functional Connectivity To the Lumbosacr...mentioning
confidence: 85%
See 3 more Smart Citations